THE COMPETITIVENESS OF ANIMAL PRODUCTS FROM THE REPUBLIC OF MOLDOVA: THE VALUE CHAIN APPROACH - Artur GOLBAN; Rita GOLBAN; Alexandru GORGOS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The competitiveness of an enterprise depends on the competitiveness of the offered products on the market, being based on the comparative characteristics analysis of the analyzed product with the competing products from the market, in order to satisfy specific needs and being acceptable by the customer in terms of price. The animal products from the Republic of Moldova play a significant role in the economic growth of the country. The scientific research is dedicated to the analysis of the competitiveness of animal products from the Republic of Moldova using the value chain method, namely were analyzed the elements of the animal products value chain, the problems of the agricultural producers at the level of animal products value chain, the marketplace of animal products. As a result of the performed investigations there were proposed recommendations in order to increase the competitiveness of animal products from the Republic of Moldova.